Adverse Reactions Caused by Biomaterials Used in Dentistry - Marco Antonio Mesache Villagómez; María Daniela Morales Núñez; Gabriela Vaca Altamirano (Medisur)
A dental biomaterial is the material used in dental practice, except drugs, that interacts with living tissues and performs a particular function without causing damage, both local and systemic, to the host, so the objective of this bibliographic review is to describe the main adverse effects caused by the most widely used dental biomaterials in the dental field. Articles published in the databases were reviewed: Medline through PubMed and Elsevier through Science Direct. The equation used for the search was: (Biocompatible Dental Materials) and (Side Effects). The period covered for the research was from January 2017 to June 2022. 309 articles were found and only 8 of them met the inclusion criteria. The results presented in this research may alert dental professionals to the use of various materials that have been shown to have cytotoxic effects. The most biocompatible materials were: ProRoot, BioRoot-RCS, Bulk Flow, Optibond Solo Plus, Adhese Universal, Vita Enamic, Lava Ultimate, Vita AC-12, InSync, Poligrip Flavor Free Fixative Cream Ketac Molar, Ionofil Molar, Twinky Star. While that the least biocompatible were: Biopulp, Durphat, Fixodent Pro Duo Protection and Fixodent Pro-Plus Duo Protection.